Against the stronghold city: on the core value of 'being together' - Decandia, Lidia (Scienze del Territorio, 2024)
By developing our awareness of the challenges posed by the continuous migratory movements that traverse our lands, this article encourages us to reflect upon the deep meaning of the word ‘city’. It challenges the idea that the city can only be identified as that stable, circumscribed form, the hub of territorial control, the place where power is centralised and production surplus accumulated and where the foreign and the diverse have to be kept at the edges, and it attempts to question again the origin of this phenomenon. It takes up Mumford’s constructive insights once more, confirmed by the archaeological discoveries of recent decades, and proposes that the deep core of the ‘urban’ be traced back to those sacred places for ceremonial meetings, where peoples that came from different parts converged to celebrate being together, with brief rituals and festivals linked with the course of the seasons, the passing of time, the cyclic nature of life and the cult of ancestors. This meditation on the roots leads to the seed enclosed within the word ‘city’ being expanded to take on a new meaning, of which we have however always been aware: that of a relational, collective work, never a cut-and-dried fact – a concern that must be continuously and creatively reimagined, indeed through the sharing and pooling of different ways of life and the interaction and exchange between diversities.